The Electroencephalogram in Febrile Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
The clinical value of EEG investigations in children with febrile seizures is reviewed from the Section of Child and Adolescent Psychiatry, Parke Hospital for Children, Old Road, Hedington, Oxford, England.